Ultrasound-Guided Regional Anesthesia Under Sedation for Radical Mastectomy in an SAS Patient: A Case Report - Zhang, Na; Wang, Tingting; Wei, Penghui; Zhou, Jinfeng; Li, Jianjun (Frontiers in Oncology, 2021)
Radical mastectomy is commonly performed under general anesthesia, and regional block is often used as assisted or postoperative analgesia. We herein report a case of successful radical mastectomy with severe aortic stenosis (SAS) by using ultrasound-guided regional anesthesia under sedation. A 66-year-old female with an American Society of Anesthesiology physical status IV; limited functional capacity with <4 metabolic equivalents; a lump (10 cm × 8 cm) in the right breast with skin breakage and infection; and a history of hypertension, diabetes, atrial fibrillation, and SAS, underwent lump-resection and rapid pathological examination by biopsy. Considering a high-risk of significant mortality, we used ultrasound-guided regional block to avoid general anesthesia. We performed the right thoracic paravertebral nerve block (TPVB), subclavicular brachial plexus block, and pectoralis plane block (PECS 1). Patient tolerated the procedure well with no significant hemodynamic changes. Nevertheless, when the axillary lymph nodes were wiped, discharge was observed from the patient’s upper limbs. We inserted the laryngeal mask airway combined with low-dose sevoflurane inhalation sedation. The operation was successfully completed, and the patient was revived with steady hemodynamics and good prognosis. In the present case, radical mastectomy with SAS was performed successfully using ultrasound-guided regional anesthesia under sevoflurane sedation. Despite some potential limitations, this case report can serve as a reference for other anesthetists.